Design of self-testable wafer-scale processor arrays - CHOI, YOON-HWA (International journal of electronics, 1990)
A technique for designing self-testable wafer-scale arrays is presented. Faulty and Fault-free cells (processors, PEs) are indentified in distributed fashion without providing correct responses from the outside. It uses both local comparisons and dissemination of the comparison results. Faults in diagnostic circuits, which have been typically assumed to be fault-free, are also covered by the self-testing algorithm. The algorithm is quite general in the sense that it is independent of the structure of the syndrome analyser in each cell.